Pengaruh Konteks Teman Sebaya Terhadap Keterlibatan Belajar dengan Mediator Self-System Processes - Lilim Halimah; Sulisworo Kusdiyati; Susandari Susandari (Psympathic : Jurnal Ilmiah Psikologi, 2017)
High school students in the city of Bandung occupy the largest population compared to other cities in West Java, The Central Bureau of Statistic data shows an imbalance between the number of students with rough participation rate and net enrollment rate. The purpose of this study is to determine the influence of peer context to the student engagement of high school students in Bandung with self-system processes as a mediator variable. The method of this research is causality correlation. The sample of 632 students were selected using Random Sampling Techniques from 8 public High Schools in Bandung. The questionnaire measured peer context, self-system processes, and student engagement, which were based on Connell's theory. Data analysis was Partial Least Square (PLS) method. Results show that there is influence of peer context on government high school student’s engagement in Bandung with self-processing system as a mediator variable. There is influence of sense of relatedness, sense of autonomy, and sense of competence on the student engagement. The student engagement of high school in Bandung is in the medium category.